The Differential Impact of Learning Experiences on International Student Satisfaction and Institutional Recommendation - Ammigan, Ravichandran; Dennis, John Lawrence; Jones, Elspeth (Journal of International Students, 2021)
This research uses i-graduate’s International Student Barometer to investigate whether overall satisfaction and institutional recommendation are influenced by student nationality and destination country, while controlling for the covariates of learning experiences. The result of our analysis is the identification of a conceptual framework for the differences between evaluations (reflecting satisfaction with an experience) and behavioral intentions (willingness to recommend that experience to others), and this important frame has consequences for how institutions recruit and retain international students. These results indicate that student nationality, destination country, and learning experience differentially influence both overall satisfaction and institutional recommendation. The study finds that student nationality and destination country significantly influenced both satisfaction and recommendation. While learning experience “teaching” variables (“program organization” and “quality of lectures”) mattered most for overall satisfaction, “study” variables (“English language support” and “employability skills”) were mainly associated with institutional recommendation.